Studien zum Gottesbild im Johannesevangelium - Burz-Tropper, Veronika (Mohr Siebeck, 2020)
The whole of the New Testament is occupied with God and the discussion of him. New Testament scholarship, however, barely treats God the Father as a separate subject. Because His significance is not to be neglected, the contributors to this volume turn their attention to illuminating God the Father from various angles.